Sustained Remission in Patients with Primary Immune Thrombocytopenia after Romiplostim Tapering and Discontinuation: A Case Series in Real Life Management in Spain - María-Eva Mingot-Castellano; Carlos Grande-García; David Valcárcel-Ferreiras; Clara Conill-Cortés; Loreto de Olivar-Oliver (Case Reports in Hematology)
Romiplostim, a thrombopoietin-receptor agonist (TPO-ra), is a highly effective option in primary immune thrombocytopenia (ITP), with 80–90% of patients achieving platelet responses after few weeks of treatment. The evidence showing remissions, that is, sustained platelet counts after romiplostim discontinuation, in patients with ITP refractory to immunosuppressive therapy is steadily increasing. However, there is a lack of guidelines or recommendations addressing how and when to taper romiplostim in clinical practice in patients maintaining elevated and stable platelet counts. Furthermore, given the high heterogeneity of ITP patients, no associated predictive factors have been currently identified. Here, we present 4 representative clinical cases of the daily clinical practice in Spain comprising newly diagnosed, persistent, and both splenectomized and nonsplenectomized chronic ITP patients treated with romiplostim, achieving and maintaining clinical remission (platelet count ≥ 50 × 109/L for 24 consecutive weeks in the absence of any treatment for ITP) after treatment tapering and discontinuation, without observed safety concerns. Prospective studies identifying clinical and biological predictive factors of sustained response are warranted.